The exponential equation is in the form of y = a^{x}, where 'a' is positive real number and x is the variable. If base of the exponential equation is same on the equal sides, then the equation solved by using the property, if b^{x} = b^{y}, then x = y, where b > 0 and b $\neq$ 0.

**For example,** the equations x^{2} - 2 = 0 and x^{4} - 4 x^{2} + 4 = 0 are exponential equations.

**Below are given examples of solving exponential equations with steps of explanation:**

**Exponential Equation 1:**

Solve 3^{2x–1} = 27

**Solution: **

In this case, exponential on one side "equals" and a number on the other.

Solve the equation and express the "27" as a power of 3. Since 27 = 3^{3},

3^{2x–1} = 27

3^{2x–1} = 3^{3}

2x – 1 = 3

2x = 4

x = 2

The Exponential equation answer x is 2

**Exponential Equation 2:**

Solve for x in the equation e^{x} = 80

**Solution:**

Step 1: Take the natural log of both sides: log (e^{x}) = log(80)

Step 2: Simplify the left part of the above equation using Logarithmic Rule ---> x log (e) = log(80)

Step 3: Simplify the left part of the above equation: Since log (e) = 1, the equation reads x = log (80)

log (80) is the exact answer and x = 4.38202663467 is an approximate answer because we have rounded the value of log (80).

**Example:** Solve for x in the equation 10^{x + 5} - 8 = 60

**Solution:**

Step 1: Isolate the exponential term before we take the general log of both sides. Therefore, add 8 to both sides: 10^{x + 5} = 68

Step 2: Take the common log of both sides:

log (10^{x + 5}) = log (68)

Step 3: Simplify the left part of the above equation using Logarithmic Rule 3:

(x + 5) log (10) = log (68)

Step 4: Simplify the left part of the above equation: Since log (10) = 1, the above equation are given (x + 5) = log (68)

Step 5: Subtract 5 from both sides of the above equation:

x = Log (68) - 5

x = -3.16749108729 is an approximate answer.

Related Calculators | |

Exponential Equation Calculator | Calculate Exponential |

Exponential Distribution Calculator | Graphing Exponential Functions Calculator |